Determinants of chronic energy deficiency (CED) incidence in pregnant women: A cross-sectional study in Banyumas, Indonesia - Wati, Erna K.; Murwani, Retno; Kartasurya, Martha I.; Sulistiyani, Sulistiyani (Narra J, 2024)
Chronic energy deficiency (CED) in pregnant women is a condition of energy and protein deficiency that lasts for years and causes problems in the mother and fetus. Due to its significant consequences, determining the determinants associated with CED incidence is of utmost importance. The aim of this study was to determine the determinants of the incidence of CED in pregnant women in Indonesia. A cross-sectional study was conducted on pregnant women in Banyumas, Central Java, Indonesia, in 2022. Plausible determinants included maternal age, pregnancy interval, parity, educational attainment, nutritional knowledge, employment, frequency of antenatal care (ANC), and nutritional intake. The Chi-squared test followed by multivariate logistic regression were used to determine the factors associated with the incidence of CED. Our data indicated that 32% of the pregnant women had CED. Univariate analysis found that maternal age (p=0.022), pregnancy interval (p=0.009), educational attainment (p=0.012), knowledge of nutrition and CED (p=0.023), frequency of utilization of ANC services (p=0.028), energy intake (p=0.002), protein intake (p=0.006), vitamin C intake (p=0.016), folate intake (p=0.011), and calcium intake (p=0.004) were significantly associated with CED incidence in the pregnant women. Multivariate analysis indicated that extreme maternal age (OR; 3.49; 95%CI: 1.10–11.05), low educational attainment (OR: 4.12; 95%CI: 1.37–12.33), short pregnancy interval (OR; 7.30; 95%CI: 1.84–28.99), low frequency of ANC (OR: 3.06; 95%CI: 1.01–9.19) and low protein intake (OR: 6.80; 95%CI: 1.62–28.59) were associated with CED incidence. This study underscores the importance of increasing nutritional intake, frequency of ANC, and pregnancy interval among pregnant women to reduce the risk of CED and its adverse health outcomes.